PTU-060 Burden of liver disease in the west midlands: alcoholic liver disease hospital admissions increased. (17th June 2017) - Bhala, N; Haroon, S; Burwood, S; Pennell, C; Carter, H; Daley, A; Day, E; Sharkaway, A El; Ferguson, J; Freshwater, D; Gordon, V; Holt, A; et al.
Abstract : Introduction: Liver disease is a leading cause of premature death and a rising cause of hospital admissions in the UK. We sought to assess the clinical burden of common liver diseases in the West Midlands assessed by hospital admissions regionally. Method: Routine data from PHE Alcohol and Liver Disease West Midlands Profiles from 2013–16 were assessed. Sources include the Office of National Statistics (ONS) and NHS Digital Hospital Episode Statistics (HES). Specific diseases assessed include: alcoholic liver disease (ALD); non-alcoholic fatty liver disease (NAFLD); chronic viral hepatitis B and C; and hepatocellular cancer (HCC). Results: Age-standardised hospital admissions for all liver disease were lower than the national average, especially in males. However, hospital admission rates for ALD were higher (34.3 per 100, 000) for both men and women compared to the national average (31.9). Coventry (54.9), Telford and Wrekin (53.7), Wolverhampton (43.5), Birmingham (41.9) and Worcestershire (41.8) were amongst the highest areas in the region. Solihull (12.3), Shropshire (25.0) and Staffordshire (26.0) were amongst the lowest areas. Hospital admission rates for chronic viral hepatitis related end-stage liver disease/HCC were similar to the national average, and those for NAFLD were lower than the national average. Conclusion: Hospital admissions for alcoholic liver diseases are significantly higher in West Midlands compared to the rest of England. A collaborative liver health network in the West Midlands is required to help tackle the burden of preventable liver disease admissions. References: . Chief Medical Officer Annual Report on Liver Disease2012 . Lancet Liver Commission Lancet2014 Disclosure of Interest: None Declared